European Study Programme for Advanced Networking Technologies - Vaz de Carvalho, C.; Salonen, J.; Bjorn, K.; Knockaert, S.; Van Steenberghe, R.; Schoofs, L.; Rugelj, J.; Marzo, J. L (Elektronika ir Elektrotechnika, 2010)
In this article authors present main objectives and progress of the EU ERASMUS CD project: European Study Programme for Advanced Networking Technologies (ESPANT). Participants from Belgium, Spain, Finland, Portugal and Slovenia are involved in this project. Major novelties in the development of one year study programme curriculum - long lifelong learning oriented - are presented. In ESPANT a professional competences approach is addressed, therefore Syllabus contents and activities are practical oriented. Their structure and didactic units description are also described. The comments from a resonance group (formed by academia and industry members) are also summarized as a crucial methodology to develop ESPANT.